ATENEA Artificial intelligence for elderly people: No more Buttons, Menus os Tactile Screens. With ATENEA, by a Voice Conversation, Everything is Possible - Isern, Albert (Street Art & Urban Creativity, 2025)
ATENEA is a NextGenerationEU project managed by the Social Rights Ministry of the Government of Catalonia. ATENEA uses a mobile phone customized with an extremely simplified user interface that requires only voice interaction (voicebot). This allows elderly people with limited digital literacy, to request city services, simply through conversation. The ATENEA system manages these requests on their behalf via the corresponding online services. Elderly people find themselves in vulnerable situations, as managing tasks online often becomes an impossible mission. The digital divide isolates, increasing the perception of unwanted loneliness, one of the key social determinants of health.